2009
DOI: 10.3892/or_00000483
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the tumor suppressor ARHI inhibits the growth of pancreatic cancer cells by inducing G1 cell cycle arrest

Abstract: Abstract.A Ras homologue member I (ARHI) is an imprinted tumor suppressor gene whose expression is frequently lost in pancreatic cancers. This small GTP-binding protein is a member of the Ras superfamily with significant homology to Ras. In contrast to the Ras oncogene, ARHI has been shown to have anti-proliferative effects, but the mechanisms by which it inhibits pancreatic cancer cell proliferation and induces cell cycle arrest remain unclear. By generating stable transfectants, ARHI was reexpressed in pancr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…DIRAS3 was also downregulated or lost in pancreatic cancers compared with its wide expression in ductal and acinar cells of normal pancreatic tissue (Y. Q. Hu et al, 2013;Lu et al, 2009;Yang et al, 2010). Similar result was found in pancreatic endocrine tumors, that DIRAS3 expression showed a statistically significant difference between either normal pancreas or well-differentiated endocrine tumors and poorly differentiated endocrine carcinomas (Dalai et al, 2007).…”
Section: Diras3 and Cancersupporting
confidence: 65%
See 3 more Smart Citations
“…DIRAS3 was also downregulated or lost in pancreatic cancers compared with its wide expression in ductal and acinar cells of normal pancreatic tissue (Y. Q. Hu et al, 2013;Lu et al, 2009;Yang et al, 2010). Similar result was found in pancreatic endocrine tumors, that DIRAS3 expression showed a statistically significant difference between either normal pancreas or well-differentiated endocrine tumors and poorly differentiated endocrine carcinomas (Dalai et al, 2007).…”
Section: Diras3 and Cancersupporting
confidence: 65%
“…Moreover, Lu et al (2009) proved increase of p21 (WAF1/CIP1) and p27 kip1 , decrease of cyclins A and D1, along with activity reductions of cyclin-dependent kinases 2 (CDK2) and CDK4 in DIRAS3 transfected cells. However, Rosen et al (2004) revealed that DIRAS3 expression is only correlated with the expression of p21 (WAF1/CIP1) but not with cyclin D1 in clinical epithelial ovarian cancers.…”
Section: How Diras Family Members Regulate Cell Growthmentioning
confidence: 92%
See 2 more Smart Citations
“…The recent studies have been found that BRCA2, BRCA1, PALB2, STK11/LKB1, SOX15 genes and TGFBR1, TGFBR2, or ACVR1B receptors [60][61][62][63][64][65][66][67][68] are inactivated in a small subset of PC. In addition, ARH1 and KLF4 genes may be candidate in pancreatic tumorigenesis [69][70][71][72].…”
Section: Tumorsupressor Genesmentioning
confidence: 99%